단지형 한옥건축물의 가치와 사례분석 - 김종득(Kim, Hyun Min) (한국디자인리서치, 2017)
최근 들어 한옥 건축물은 건강한 삶의 질을 높이고 문화적 요소를 충족시킬 수 있는 공간으로서 자리 매김 하고 있다. 한옥 건축물은 역사적 가치와 예술적 가치를 공유하며, 문화적 유산으로서의 그 가치를 높이고 있다. 부동산의 차별화가 요구되는 시기에 한옥 건축물의 대명사로 알려진 사찰, 고택 등에서 벗어나 새로운 주택, 상업, 숙박시설 등으로 발전시켜 나가야 할 것이다. 우리의 한옥 건축물은 독특한 아름다움과 안락함을 제공하지만 근대화와 더불어 서양식 생활방식과 경제논리 및 편의주의로 인하여 한옥 건축물이 불편의 대명사로 치부되어 60년대 들어서 새마을 운동과 현대화 산업의 일환으로 쉽고 빠르게 지을 수 있는 콘크리트 건축물이 부각되면서 우리의 한옥 건축물은 철거의 대상이 되었다. 그러나 한옥 건축물은 현대인이 추구하는 친환경, 안락함, 문화적 욕구를 충족시킬 수 있는 요소들을 가지고 있다. 우리 선조들의 지혜와 사상을 계승할 수 있는 한옥에 대한 연구 개발 노력이 다방면에서 진행되고 있다. 한민족의 정체성을 상징하며 역사성과 문화적 가치를 간직한 한옥을 관광자원화 함으로서 지역사회의 활성화에도 기여할 수 있을 것이다. 한옥 건축물이 갖는 특성과 도시 맥락에 부합되는 기능을 부여하여 과거의 건축물로서 가치를 보존하며 현재의 특성을 살린 활용을 통한 미래의 생활공간으로 재생시켜 개인과 지역사회 발전에 기여 할 수 있을 것이다. 본 논문은 점차 시들어 가고 있는 우리의 전통한옥 건축물을 발전시켜 우리의 전통주거 와 삶, 인간과 공존하는 동반자가 될 수 있도록 개선하며 보전하여 후세에 물려 줄 때 그 가치가 더욱 클 것이다. Recently, Korean-style houses can improve quality of life and fulfill cultural factors. Space is being positioned as a space. Traditional Korean houses share historic values and artistic values, increasing their. Our hanok structure is unique to modern conveniences, but in addition to modernization and convenience of modern living styles and conveniences, the structure of hanok structures in Hanok Complex and the modern style of modern buildings became the subject of demolition. However, Korean-style houses have elements that cater to eco-friendly, comfortable, and cultural needs pursued by modern people. Research and development efforts are underway in various aspects of Hanok, which can succeed in the wisdom and wisdom of our ancestors. The revitalization of the hanok, which symbolizes the identity of the Korean people and the cultural values of the Korean people, can also contribute to revitalization of the community. It will be able to preserve the characteristics of the existing buildings and contribute to urban development by utilizing the characteristics of the existing architecture and the ability to preserve the characteristics of the existing characteristics. This paper will further enhance the value of our traditional hanok houses, which are gradually becoming extinct, and will become more valuable to us as we strive to become allies of our traditional hanok, life and human beings. KCI Citation Count: 0